1999
DOI: 10.1046/j.1365-3032.1999.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition in Yponomeuta cagnagellus: the importance of contact cues for host plant acceptance

Abstract: Summary Small ermine moths (Yponomeutidae: Lepidoptera) are specialist herbivores. Species within the genus Yponomeuta are each specialized on a limited number of plant species, mainly within genera belonging to the Celastraceae. European Yponomeuta species have developed new specialized host affiliations, mainly on rosaceous hosts. Since these host shifts are reputed to be of consequence for speciation, the role of the ovipositing female is of particular interest. Study of the pre‐oviposition behaviour of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…albicana . Insects, through evolution and divergence, may evolve different behavioral characteristics [52]. Accordingly, we found the differences on the antennal sensilla of C .…”
Section: Discussionmentioning
confidence: 72%
“…albicana . Insects, through evolution and divergence, may evolve different behavioral characteristics [52]. Accordingly, we found the differences on the antennal sensilla of C .…”
Section: Discussionmentioning
confidence: 72%
“…Oviposition in Lepidoptera is largely mediated by specific non‐volatile host compounds perceived by gustatory sensilla (Renwick & Chew, 1994; Schoonhoven et al., 1998). In Y. cagnagellus , for instance, adult host acceptance is based on non‐volatile plant‐surface chemicals (Hora & Roessingh, 1999a,b). In the present paper, we show that this is also the case for the closely related Y. padellus .…”
Section: Discussionmentioning
confidence: 99%
“…Lepidoptera will in general oviposit on artificial substrates if the appropriate leaf surface compounds are present. In Y. cagnagellus , it has been demonstrated that the surface extracts of host plants are sufficient to stimulate oviposition (Hora & Roessingh, 1999b), indicating that gustation is the principal mode of perception involved in adult host acceptance. In Y. padellus this is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale and method of analysis is described by Parr et al (1996) and Hora & Roessingh (1999). The goodness-of-fit of the log-linear model was assessed using a likelihood ratio statistic (G tests).…”
Section: Discussionmentioning
confidence: 99%